Relationship between Selection Factors, Food Acceptability, and Intake with Nutritional Status in Orphanage Children in South Jakarta - Agiratama, Nanda Putri; Kurniasari, Rarih; Sefrina, Linda Riski (Jurnal Kesehatan Pasak Bumi Kalimantan, 2024)
Background: Food selection and food acceptability can influence eating habits and nutrient intake. Negative eating habits and intake levels that do not meet the body's needs can cause problems with nutritional status. This includes children in orphanages, which have limited food provision and are therefore less able to provide food according to standard needs. Objective: To analyze the relationship between food selection factors, food acceptability, and intake with nutritional status in orphanage children in South Jakarta. Methods: This study used cross sectional with analytic observational method. Sampling using purposive sampling method. Statistical tests using the Gamma test. Results: The results showed that there was a relationship between ethical problem factors (0.004) and energy intake (0.032) with nutritional status but there was no relationship between mood factors (0.672), comfort factors (0.349), sensory factors (0.465), factor of natural content in food (0.774), price factor (0.138), weight control factor (0.609), familiarity factor (0.293), food acceptability (0.129), protein intake (0.097), fat intake (0.116), and carbohydrate intake (0.233) with nutritional status in orphanage children.Conclusion : There is a relationship between ethical factors and energy intake with nutritional status.